Social Entrepreneurship in the Economic Ecosystems of Latin America. An Alternative in Times of Global Crisis - Guilarte-Barinaga, Elizabeth (2023)
Through a bibliometric analysis and multivariate statistical analysis techniques, the theoretical structure of social entrepreneurship was analyzed through the exploration and determination of the relationship between the dimensions and variables that make up this construct. The research allowed determining the relationships between four dimensions with their corresponding variables: social, governmental, strategic promotion of social entrepreneurship and social research device. It was found that, in the countries with better development in the field of social entrepreneurship, there was a balance between its theoretical and practical development. Social research devices were highlighted to provide a theoretical basis and use the information and knowledge management framework. It was also revealed that the most developed economies, paradoxically, are those that show the best theoretical and practical indicators of social entrepreneurship, in contrast to developing countries, where the solution to social problems accumulated for centuries, in a sustainable way, is more imperative. On the other hand, social entrepreneurship can contribute to the Sustainable Development Goals in countries with weaker economies, but its promotion must be planned and applied with a practical approach, based on economic-commercial development that supports the romantic or political ideal.